Tourism in Latin America: Cases of Success - Panosso Netto, Alexandre (Springer, 2015)
This book presents eleven case studies of success about Latin America tourism. The cases are embedded in a framework describing the economic and cultural foundations of tourism development in the continent. Mexico, Brazil, Chile and Costa Rica are some of the Latin countries which have become examples and models for touristic development, respect for the environment and social inclusion. The book showcases some of the best practices, along with an analysis of how these projects helped improving the environmental and social surroundings and how return on investments has been ensured. Latin America is shown as an excellent example, with the Gross Domestic Product of the continent expanding intensely in the tertiary sector like leisure, hospitality, travel, tourism, entertainment, gastronomy, events and indoor and outdoor recreation. This book is a valuable resource both for professionals in the tourism industry and for researchers in tourism management.